CORRUPTION IN ASIA PACIFIC - Nelly Masnila; darusalam darusalam (University of Sang Bumi Ruwa Jurai, 2018)
This study was conducted to investigate the effect of economic development (GDP and GNI) on corruption (Corruption Perception Index) in Asia Pacific countries. The data used were obtained for 21 selected countries samples during the period 2010-2016. For this data panel, we use Eviews program to analize it. The results of this study shows that first, simultantly, all variables GDP, GNILN, and GNIGR have positive and significant effect on corruption. Second, partially GDP has negatif effect and GNILN has posistif effect on corruption. Third, although the statistical results of this study prove that GDP and GNI have an influence on corruption, it stands that the countries with the highest CPI are not the countries with the highest GDP and GNI. Similarly, countries with the lowest CPI is not the country with the lowest GDP/GNI